Colorimetric Detection of Class A Soybean Saponins by G-Quadruplex-Based Hybridization Chain Reaction. (5th November 2020) - Yin, Congcong; Zhao, Qiaoling; Yue, Aiqin; Du, Weijun; Liu, Dingbin; Zhao, Jinzhong; Zhang, Yongpo; Wang, Min
Abstract : Soybean saponin is one of the important secondary metabolites in seeds, which has various beneficial physiological functions to human health. GmSg-1 gene is the key enzyme gene for synthesizing class A saponins. It is of great significance to realize the visual and rapid detection of class A saponins at the genetic level. The hybridization chain reaction (HCR) was employed to the visual detection of GmSg-1 gene, which was implemented by changing the length of the target fragment to 92 bp and using the hairpin probes we designed to detect the GmSg-1 a and GmSg-1 b genes. The best condition of HCR reaction is hemin (1.2  μ M), Triton X-100 (0.002%), ABTS (3.8  μ M), and H2 O2 (1.5 mM). It was found that HCR has high specificity for GmSg-1 gene and could be applied to the visual detection of different soybean cultivars containing Aa type, Ab type, and Aa/Ab type saponins, which could provide technical reference and theoretical basis for molecular breeding of soybean and development of functional soybean products.